2016
DOI: 10.1109/access.2015.2514261
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid MIMO Architectures for Millimeter Wave Communications: Phase Shifters or Switches?

Abstract: Hybrid analog/digital MIMO architectures were recently proposed as an alternative for fully-digitalprecoding in millimeter wave (mmWave) wireless communication systems. This is motivated by the possible reduction in the number of RF chains and analog-to-digital converters. In these architectures, the analog processing network is usually based on variable phase shifters. In this paper, we propose hybrid architectures based on switching networks to reduce the complexity and the power consumption of the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
659
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 773 publications
(699 citation statements)
references
References 81 publications
3
659
0
Order By: Relevance
“…This observation confirms the derived analytical expressions in Theorem 2 and Corollary 3. Meanwhile, Figure 2 also provides the total achievable SE for the full digital architectures [43], as well as the hybrid architectures with the ideal phase shifters and switch network [19]. It is shown that the total achievable SE of full digital architectures always outperforms the one of hybrid architectures, regardless of ideal phase shifters, switch network, and DFT precessing.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This observation confirms the derived analytical expressions in Theorem 2 and Corollary 3. Meanwhile, Figure 2 also provides the total achievable SE for the full digital architectures [43], as well as the hybrid architectures with the ideal phase shifters and switch network [19]. It is shown that the total achievable SE of full digital architectures always outperforms the one of hybrid architectures, regardless of ideal phase shifters, switch network, and DFT precessing.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The detailed energy consumption is provided by LAN = 20 × 10 −3 Watt, PS = 30 × 10 −3 Watt, SW = 5 × 10 −3 Watt, FR = 40 × 10 −3 Watt, cod = 4 Watt, and dec = 500 × 10 −3 Watt, and assume that the efficiency of transmitter power is = 0.5 at the BS. These above parameters are obtained from the results of [19,37] for hybrid architectures. Figure 5 displays the total achievable EE as a function of the input SNR.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations